BANGUNAN HIJAU PADA PUSAT TANAMAN HIAS DI KOTA RANTAU - Kamil, Muhammad Septian; Rahman, Akbar (UNIVERSITAS LAMBUNG MANGKURAT, 2023)
Ornamental plants are plants that function as decorations in space, both outdoors and indoors. Collecting ornamental plants is very popular among housewives. Based on a survey conducted in Rantau City, the use of ornamental plants in houses in urban areas is very little compared to rural areas. This indicates that people in urban areas are less concerned about ornamental plants. To introduce ornamental plants more deeply to all circles, an ornamental plant center is made that can accommodate plants efficiently. The problem raised in the design of the ornamental plant center is how to design a building that can accommodate plants, attract public interest and accommodate activities related to ornamental plants. This problem is solved by using a building form in the form of a greenhouse to accommodate massive plants, and using the concept of green building to optimize the workability of the building and introduce ornamental plants to a wider community.